Diversity and Abundance Dragonflies (Odonata) at Mount Sigogor Nature Reserve Area, Ponorogo Regency, East Java, Indonesia - Muhamad Azmi Dwi Susanto; Saiful Bahri (Biota, 2021)
Mount Sigogor Nature Reserve area is a mountainous tropical rain forest, administratively located in Pupus Village, Ngebel District, Ponorogo Regency, East Java, Indonesia. One of the main functions of this nature reserve is as a water catchment area for the villages around the nature reserve area. Water sources and flows within the Mount Sigogor Nature Reserve area have the potential as natural habitat for dragonflies. This study aims to determine the diversity and abundance of dragonflies (Odonata) in the Mount Sigogor Nature Reserve Area. The method of collecting dragonflies data used the Visual Day Flying method by recording the diversity of dragonflies species and counting the number of individuals from each observed dragonflies species. The data obtained were analyzed using the Relative abundance, Shannon-Wiener Heterogeneity Index and the frequency of Presence. The results of the research conducted showed that there were 14 species from 7 families with a total of 464 individuals. The Shannor-Wiener diversity index shows that the diversity value is H'= 1.81. Meanwhile, the presence frequency analysis showed that there were four species with a value of 100% which were classified as abundant Frequency of Presence, namely Euphaea variegata, Vestalis luctuosa, Rhinocypha anisoptera and Coeliccia membranipes.